Parents' knowledge of neonatal transitory conditions and their expectations of the midwife - Detka, Karolina; Gruszka, Jakub; Zwierzyńska, Anna; Dolecka-Ślusarczyk, Magdalena; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2021)
Introduction The neonatal period is the period of the child's adaptation to life outside the mother's body. The child has to adapt to the changes taking place in its body. After delivery, the new-born baby is assessed according to the Apgar scale. Objective of the study The objective of the study was to assess the parents' knowledge of the transitory conditions of neonates and to identify their expectations towards medical personnel. Material and methods 248 women participated in the study. Inhabitants of large cities accounted for 64.5% of the respondents and 16.2% of the respondents were inhabitants of rural areas. Women aged over 35 accounted for 46.8% of patients, 19.3% were patients between the ages of 26 and 30. Patients between the ages of 30 and 35 also accounted for 19.3%. Patients under 25 years of age accounted for 14.6%. The Bioethics Committee approved the project. Statistical analysis was performed with the use of the Statistica computer program. Results 81% of women displayed knowledge about the duration of the neonatal period. 62% of the respondents knew the effect of vitamin K in preventing the occurrence of haemorrhagic disease in the neonate. Half of the women prefer to feed on demand. A big problem among women in childbed is the lack of access to a psychologist. Conclusions Parents cannot recognize transitory conditions in a neonate. Antenatal education of future mothers influences their pro-health behaviour. Parents source their knowledge from their family, friends, guides and books.